STRUKTUR KOMUNITAS ARTHROPODA PERMUKAAN TANAH DI ARBORETUM UNIVERSITAS RIAU SEBAGAI RANCANGAN HANDOUT PADA MATERI EKOSISTEM KELAS X SMA - Salmiah, Ananda; Suwondo, Suwondo; Suzanti, Fitra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the composition and diversity of soil surface arthropods at the Arboretum of the University of Riau, and obtain alternative learning resources. The method of this research is survey. The location was chosen based on purposive random sampling by considering 5 stations. The parameters used in this study are type composition, population density (ind / m ^ 2), diversity index (H '), dominance (C), similarity index (S), wealth index (d), for physical parameters including temperature soil, soil moisture, light intensity, soil pH, organic matter content. The data obtained are presented in a table then analyzed descriptively to be associated with the learning material. Based on the results of the research that has been carried out, there are differences in the composition of soil surface arthropods at each research station. Of the five stations, the soil surface arthropods obtained consisted of 4 orders and 11 species. The order was found which consisted of Hymenoptera, Collembola, Orthoptera, Coleoptera and Diptera. At the first station, 385 individuals were found. At the second station, 239 insects and 255 insects were found at station III. insects and found 196 IV stations, and insects and found 212 units V. Soil arthropod studies in the Arboretum area of the University of Riau in this study were one form of learning activities that would help students understand ecosystem material that included abiotic components and biotic components of Arboretum. Key Words: Composition, Diversity, Soil Surface, Arthropods